Sarcocystis masoni, n. sp. (Apicomplexa: Sarcocystidae), and redescription of Sarcocystis aucheniae from llama (Lama glama), guanaco (Lama guanicoe) and alpaca (Vicugna pacos) - Moré, Gastón Andrés (2016)
There is considerable confusion concerning the species of Sarcocystis in South American camelids (SAC). Several species names have been used; however, proper descriptions are lacking. In the present paper, we redescribe the macroscopic sarcocyst forming Sarcocystis aucheniae and describe and propose a new name, Sarcocystis masoni for the microscopic sarcocyst forming species. Muscles samples were obtained from llamas (Lama glama) and guanacos (Lama guanicoe) from Argentina and from alpacas (Vicugna pacos) and llamas from Peru. Individual sarcocysts were processed by optical and electron microscopy, and molecular studies. Microscopic sarcocysts of S. masoni were up to 800 μm long and 35-95 μm wide, the sarcocyst wall was 2·5-3·5 μm thick, and had conical to cylindrical villar protrusions (vp) with several microtubules. Each vp had 11 or more rows of knob-like projections. Seven 18S rRNA gene sequences obtained from sarcocysts revealed 95-96% identity with other Sarcocystis spp. sequences reported in the GenBank. Sarcocysts of S. aucheniae were macroscopic, up to 1·2 cm long and surrounded by a dense and laminar 50 μm thick secondary cyst wall. The sarcocyst wall was up to 10 μm thick, and had branched vp, appearing like cauliflower. Comparison of the 11 sequences obtained from individual macroscopic cysts evidenced a 98-99% of sequence homology with other S. aucheniae sequences. In conclusion, 2 morphologically and molecularly different Sarcocystis species, S. masoni (microscopic cysts) and S. aucheniae (macroscopic cysts), were identified affecting different SAC from Argentina and Peru.